The Physiological Foundations of the Wealth of Nations - Carl-Johan Dalgaard; Holger Strulik (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2011)
In the present paper we advance a theory of pre-industrial growth where body size and population size are endogenously determined. Despite the fact that parents invest in both child quantity and productivity enhancing child quality, a take-off does not occur due to a key physiological check: if human body size rises, subsistence requirements will increase. This mechanism turns out to be instrumental in explaining why income stagnates near an endogenously determined subsistence boundary. Key predictions of the model are supported by cross-country data.
Keywords: O11; I12; J13; 330; stagnation; Subsistence; Nutrition; Body size; Population growth